Chronological T‐wave alternation before and after the onset of arrhythmogenic right ventricular cardiomyopathy. Issue 6 (2nd June 2022) - Sato, Akira; Saiki, Hirofumi; Kudo, Maki; Takizawa, Yurie; Kuwata, Seiko; Nakano, Satoshi; Sato, Yumi; Miura, Kunihiko; Oyama, Kotaro; Akasaka, Manami
Abstract: Identification of arrhythmogenic right ventricular cardiomyopathy (ARVC) during childhood is challenging due to the lack of specific ECG manifestation. We report chronological ECG alteration before several years of the ARVC onset in two affected children. Their ECG at the age of 6 years was almost normal for their age, and their chronological ECGs exhibited inversion of T wave in inferior leads, which are typical for ARVC, developed at younger age than that in precordial leads. In addition, the leftmost T‐wave inversion in the precordial lead shifted toward the left in our patients, which is a sharp contrast to its physiological transition. Abstract : The trend of positive conversion of the T wave in the precordial leads. The age in the horizontal axis and corresponding leftmost lead with positive T wave in the vertical axis were shown. While the physiological positive conversion of T wave, where more than 90% of general cohort show positive T wave, progresses to the right precordial leads in the normal cohort, those in the affected cohort regress with aging.